IMPROVEMENT OF ULTRASOUND DIAGNOSTICS OF BREAST BENIGN TUMORS - Nasriddinova S. Z.; Gofurova X. Z; Madumarova Z. Sh. (Scholars Digest Publishing, 2024)
The analysis of data from foreign and domestic articles published over the past 10 years on the problems of instrumental diagnosis of benign diseases of the mammary glands (BDMG). The possibilities of ultrasound X-ray mammography and magnetic resonance imaging in the differential diagnosis of various firms of BDMG and breast cancer are described. The importance of using the BI—RADS system in describing the results of radiation methods for diagnosing breast diseases is shown.
Keywords: benign diseases of the mammary glands, radiation diagnostic methods.